Pelatihan Pelaksanaan K3 Terhadap Risiko Kebakaran Di Madrasah Ibtidaiyah Al Huda - Pratiwi Setyaning Putri (Terang, 2020)
Indonesia is the most vulnerable country to disasters in the world based on data released by the United Nations Agency for the International Strategy for Disaster Risk Reduction (UN-ISDR) [1]. This will certainly have an impact on the number of fatalities if there is no understanding and good handling of the parties involved. Alert and alert attitudes are still very minimal and are often not taught in formal teaching and learning activities. In addition to human resources, disaster risk reduction can also be pursued by providing adequate K3 facilities in each building. Madrasah Ibtidaiyah Al Huda which is on Jalan Al Huda Rawasapi RT 02/09 Kelurahan Jatimulya - Tambun Selatan Bekasi District has a moderate earthquake risk. In addition, the location of schools that are not on the main road and access roads to locations that are relatively difficult to pass by fire trucks make it vulnerable in the event of a fire disaster. The solution offered is education of OHS implementation of disasters and the provision of facilities and infrastructure to deal with these disasters. The expected output targets are one PKM article published through an ISSN journal, one ISBN proceeding article from a national seminar organized by STT-PLN, and publication in print / electronic media.